test_constantsimp.py 8.5 KB

123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179
  1. """
  2. If the arbitrary constant class from issue 4435 is ever implemented, this
  3. should serve as a set of test cases.
  4. """
  5. from sympy.core.function import Function
  6. from sympy.core.numbers import I
  7. from sympy.core.power import Pow
  8. from sympy.core.relational import Eq
  9. from sympy.core.singleton import S
  10. from sympy.core.symbol import Symbol
  11. from sympy.functions.elementary.exponential import (exp, log)
  12. from sympy.functions.elementary.hyperbolic import (cosh, sinh)
  13. from sympy.functions.elementary.miscellaneous import sqrt
  14. from sympy.functions.elementary.trigonometric import (acos, cos, sin)
  15. from sympy.integrals.integrals import Integral
  16. from sympy.solvers.ode.ode import constantsimp, constant_renumber
  17. from sympy.testing.pytest import XFAIL
  18. x = Symbol('x')
  19. y = Symbol('y')
  20. z = Symbol('z')
  21. u2 = Symbol('u2')
  22. _a = Symbol('_a')
  23. C1 = Symbol('C1')
  24. C2 = Symbol('C2')
  25. C3 = Symbol('C3')
  26. f = Function('f')
  27. def test_constant_mul():
  28. # We want C1 (Constant) below to absorb the y's, but not the x's
  29. assert constant_renumber(constantsimp(y*C1, [C1])) == C1*y
  30. assert constant_renumber(constantsimp(C1*y, [C1])) == C1*y
  31. assert constant_renumber(constantsimp(x*C1, [C1])) == x*C1
  32. assert constant_renumber(constantsimp(C1*x, [C1])) == x*C1
  33. assert constant_renumber(constantsimp(2*C1, [C1])) == C1
  34. assert constant_renumber(constantsimp(C1*2, [C1])) == C1
  35. assert constant_renumber(constantsimp(y*C1*x, [C1, y])) == C1*x
  36. assert constant_renumber(constantsimp(x*y*C1, [C1, y])) == x*C1
  37. assert constant_renumber(constantsimp(y*x*C1, [C1, y])) == x*C1
  38. assert constant_renumber(constantsimp(C1*x*y, [C1, y])) == C1*x
  39. assert constant_renumber(constantsimp(x*C1*y, [C1, y])) == x*C1
  40. assert constant_renumber(constantsimp(C1*y*(y + 1), [C1])) == C1*y*(y+1)
  41. assert constant_renumber(constantsimp(y*C1*(y + 1), [C1])) == C1*y*(y+1)
  42. assert constant_renumber(constantsimp(x*(y*C1), [C1])) == x*y*C1
  43. assert constant_renumber(constantsimp(x*(C1*y), [C1])) == x*y*C1
  44. assert constant_renumber(constantsimp(C1*(x*y), [C1, y])) == C1*x
  45. assert constant_renumber(constantsimp((x*y)*C1, [C1, y])) == x*C1
  46. assert constant_renumber(constantsimp((y*x)*C1, [C1, y])) == x*C1
  47. assert constant_renumber(constantsimp(y*(y + 1)*C1, [C1, y])) == C1
  48. assert constant_renumber(constantsimp((C1*x)*y, [C1, y])) == C1*x
  49. assert constant_renumber(constantsimp(y*(x*C1), [C1, y])) == x*C1
  50. assert constant_renumber(constantsimp((x*C1)*y, [C1, y])) == x*C1
  51. assert constant_renumber(constantsimp(C1*x*y*x*y*2, [C1, y])) == C1*x**2
  52. assert constant_renumber(constantsimp(C1*x*y*z, [C1, y, z])) == C1*x
  53. assert constant_renumber(constantsimp(C1*x*y**2*sin(z), [C1, y, z])) == C1*x
  54. assert constant_renumber(constantsimp(C1*C1, [C1])) == C1
  55. assert constant_renumber(constantsimp(C1*C2, [C1, C2])) == C1
  56. assert constant_renumber(constantsimp(C2*C2, [C1, C2])) == C1
  57. assert constant_renumber(constantsimp(C1*C1*C2, [C1, C2])) == C1
  58. assert constant_renumber(constantsimp(C1*x*2**x, [C1])) == C1*x*2**x
  59. def test_constant_add():
  60. assert constant_renumber(constantsimp(C1 + C1, [C1])) == C1
  61. assert constant_renumber(constantsimp(C1 + 2, [C1])) == C1
  62. assert constant_renumber(constantsimp(2 + C1, [C1])) == C1
  63. assert constant_renumber(constantsimp(C1 + y, [C1, y])) == C1
  64. assert constant_renumber(constantsimp(C1 + x, [C1])) == C1 + x
  65. assert constant_renumber(constantsimp(C1 + C1, [C1])) == C1
  66. assert constant_renumber(constantsimp(C1 + C2, [C1, C2])) == C1
  67. assert constant_renumber(constantsimp(C2 + C1, [C1, C2])) == C1
  68. assert constant_renumber(constantsimp(C1 + C2 + C1, [C1, C2])) == C1
  69. def test_constant_power_as_base():
  70. assert constant_renumber(constantsimp(C1**C1, [C1])) == C1
  71. assert constant_renumber(constantsimp(Pow(C1, C1), [C1])) == C1
  72. assert constant_renumber(constantsimp(C1**C1, [C1])) == C1
  73. assert constant_renumber(constantsimp(C1**C2, [C1, C2])) == C1
  74. assert constant_renumber(constantsimp(C2**C1, [C1, C2])) == C1
  75. assert constant_renumber(constantsimp(C2**C2, [C1, C2])) == C1
  76. assert constant_renumber(constantsimp(C1**y, [C1, y])) == C1
  77. assert constant_renumber(constantsimp(C1**x, [C1])) == C1**x
  78. assert constant_renumber(constantsimp(C1**2, [C1])) == C1
  79. assert constant_renumber(
  80. constantsimp(C1**(x*y), [C1])) == C1**(x*y)
  81. def test_constant_power_as_exp():
  82. assert constant_renumber(constantsimp(x**C1, [C1])) == x**C1
  83. assert constant_renumber(constantsimp(y**C1, [C1, y])) == C1
  84. assert constant_renumber(constantsimp(x**y**C1, [C1, y])) == x**C1
  85. assert constant_renumber(
  86. constantsimp((x**y)**C1, [C1])) == (x**y)**C1
  87. assert constant_renumber(
  88. constantsimp(x**(y**C1), [C1, y])) == x**C1
  89. assert constant_renumber(constantsimp(x**C1**y, [C1, y])) == x**C1
  90. assert constant_renumber(
  91. constantsimp(x**(C1**y), [C1, y])) == x**C1
  92. assert constant_renumber(
  93. constantsimp((x**C1)**y, [C1])) == (x**C1)**y
  94. assert constant_renumber(constantsimp(2**C1, [C1])) == C1
  95. assert constant_renumber(constantsimp(S(2)**C1, [C1])) == C1
  96. assert constant_renumber(constantsimp(exp(C1), [C1])) == C1
  97. assert constant_renumber(
  98. constantsimp(exp(C1 + x), [C1])) == C1*exp(x)
  99. assert constant_renumber(constantsimp(Pow(2, C1), [C1])) == C1
  100. def test_constant_function():
  101. assert constant_renumber(constantsimp(sin(C1), [C1])) == C1
  102. assert constant_renumber(constantsimp(f(C1), [C1])) == C1
  103. assert constant_renumber(constantsimp(f(C1, C1), [C1])) == C1
  104. assert constant_renumber(constantsimp(f(C1, C2), [C1, C2])) == C1
  105. assert constant_renumber(constantsimp(f(C2, C1), [C1, C2])) == C1
  106. assert constant_renumber(constantsimp(f(C2, C2), [C1, C2])) == C1
  107. assert constant_renumber(
  108. constantsimp(f(C1, x), [C1])) == f(C1, x)
  109. assert constant_renumber(constantsimp(f(C1, y), [C1, y])) == C1
  110. assert constant_renumber(constantsimp(f(y, C1), [C1, y])) == C1
  111. assert constant_renumber(constantsimp(f(C1, y, C2), [C1, C2, y])) == C1
  112. def test_constant_function_multiple():
  113. # The rules to not renumber in this case would be too complicated, and
  114. # dsolve is not likely to ever encounter anything remotely like this.
  115. assert constant_renumber(
  116. constantsimp(f(C1, C1, x), [C1])) == f(C1, C1, x)
  117. def test_constant_multiple():
  118. assert constant_renumber(constantsimp(C1*2 + 2, [C1])) == C1
  119. assert constant_renumber(constantsimp(x*2/C1, [C1])) == C1*x
  120. assert constant_renumber(constantsimp(C1**2*2 + 2, [C1])) == C1
  121. assert constant_renumber(
  122. constantsimp(sin(2*C1) + x + sqrt(2), [C1])) == C1 + x
  123. assert constant_renumber(constantsimp(2*C1 + C2, [C1, C2])) == C1
  124. def test_constant_repeated():
  125. assert C1 + C1*x == constant_renumber( C1 + C1*x)
  126. def test_ode_solutions():
  127. # only a few examples here, the rest will be tested in the actual dsolve tests
  128. assert constant_renumber(constantsimp(C1*exp(2*x) + exp(x)*(C2 + C3), [C1, C2, C3])) == \
  129. constant_renumber(C1*exp(x) + C2*exp(2*x))
  130. assert constant_renumber(
  131. constantsimp(Eq(f(x), I*C1*sinh(x/3) + C2*cosh(x/3)), [C1, C2])
  132. ) == constant_renumber(Eq(f(x), C1*sinh(x/3) + C2*cosh(x/3)))
  133. assert constant_renumber(constantsimp(Eq(f(x), acos((-C1)/cos(x))), [C1])) == \
  134. Eq(f(x), acos(C1/cos(x)))
  135. assert constant_renumber(
  136. constantsimp(Eq(log(f(x)/C1) + 2*exp(x/f(x)), 0), [C1])
  137. ) == Eq(log(C1*f(x)) + 2*exp(x/f(x)), 0)
  138. assert constant_renumber(constantsimp(Eq(log(x*sqrt(2)*sqrt(1/x)*sqrt(f(x))
  139. /C1) + x**2/(2*f(x)**2), 0), [C1])) == \
  140. Eq(log(C1*sqrt(x)*sqrt(f(x))) + x**2/(2*f(x)**2), 0)
  141. assert constant_renumber(constantsimp(Eq(-exp(-f(x)/x)*sin(f(x)/x)/2 + log(x/C1) -
  142. cos(f(x)/x)*exp(-f(x)/x)/2, 0), [C1])) == \
  143. Eq(-exp(-f(x)/x)*sin(f(x)/x)/2 + log(C1*x) - cos(f(x)/x)*
  144. exp(-f(x)/x)/2, 0)
  145. assert constant_renumber(constantsimp(Eq(-Integral(-1/(sqrt(1 - u2**2)*u2),
  146. (u2, _a, x/f(x))) + log(f(x)/C1), 0), [C1])) == \
  147. Eq(-Integral(-1/(u2*sqrt(1 - u2**2)), (u2, _a, x/f(x))) +
  148. log(C1*f(x)), 0)
  149. assert [constantsimp(i, [C1]) for i in [Eq(f(x), sqrt(-C1*x + x**2)), Eq(f(x), -sqrt(-C1*x + x**2))]] == \
  150. [Eq(f(x), sqrt(x*(C1 + x))), Eq(f(x), -sqrt(x*(C1 + x)))]
  151. @XFAIL
  152. def test_nonlocal_simplification():
  153. assert constantsimp(C1 + C2+x*C2, [C1, C2]) == C1 + C2*x
  154. def test_constant_Eq():
  155. # C1 on the rhs is well-tested, but the lhs is only tested here
  156. assert constantsimp(Eq(C1, 3 + f(x)*x), [C1]) == Eq(x*f(x), C1)
  157. assert constantsimp(Eq(C1, 3 * f(x)*x), [C1]) == Eq(f(x)*x, C1)